Can nest predation explain the lack of defenses against cowbird brood parasitism in the Rufous-collared sparrow (Zonotrichia capensis)? - Carro, Mariana Emilia (2013)
Although interspecific avian brood parasitism usually lowers host productivity, some species lack any defense against parasites. We analyzed the effect of parasite egg removal or nest desertion following a parasitism event on the breeding productivity of the Rufous-collared Sparrow (Zonotrichia capensis), a common host of the Shiny Cowbird (Molothrus bonariensis). The Rufouscollared Sparrow is an effective cowbird host that does not eject parasite eggs. We removed cowbird eggs from nests of Rufouscollared Sparrows to test for differences in hatching, fledging, and nesting success among naturally unparasitized, parasitized, and experimentally unparasitized nests from which we removed the cowbird eggs. We also used simulations to test whether parasite egg removal or nest desertion provide viable strategies to counter the effects of parasitism in this species. Naturally unparasitized nests produced more nestlings and fledglings than parasitized and experimentally unparasitized nests, but there were no differences between parasitized nests and those from which cowbird eggs were removed. Moreover, the overall nesting success was similar for all nest types. Simulation models confirmed these results but also showed that productivity may still increase through parasite egg ejection when the nest predation rate is relaxed only if no cost of parasite egg ejection is assumed. By contrast, nest desertion was not a viable strategy to reduce the effect of parasitism. We suggest that high nest predation could reduce the benefits of antiparasite defenses in the Rufouscollared Sparrow and may help explain the lack of such behavior in this species.